A RESEARCH STUDY ON LOGISTIC AND E-COMMERCE OF AMAZON AND FLIP-KART - M. Budi Djatmiko, Rahul B. Chauhan, Nalbiy Salikhovich Tuguz, Sameer Ahmed S. Shah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
With the increasing globalization and shift in economic dominance towards southern hemisphere from the northern hemisphere in recent times, the Reverse Logistics industry has already reached at $12 billion, revealed a research by Reverse Logistics Company (RLC) during a discussion on the theme of ‘After Market Service – The New Focus of Reverse Logistics’, organized by the Confederation of Indian Industry Institute of Logistics. The logistics industry is poised to gain attention and importance in the coming days, believe the industry captains. Mr. Cyrus Guzder (Chairman, CII-IL Advisory Council & CMD, AFL Private Limited) said, “Keeping the supply chain efficient and affordable is a challenge. The logistics industry contributes about 13 per cent of GDP which is very significant but still there is a long way to go for the industry. The logistics industry needs to think deeply about the challenges.” The industry is believed yet to be at the nascent stage as only 10 per cent of sales in India take place through organized channel. Mr. P. Sreevathsa (Founder, The Service Solutions), about the challenges, said, “The industry needs to look at how a service provider can satisfy the manufacturer and in return the customer and end-consumer. Reverse Logistics is a big and emerging opportunity for the industry players in India.”